Neuroprotective and antioxidant activities of different polarity parts of the extracts of the Ginkgo biloba leaf and Zingiber officinale rhizome from Yongzhou - Huang, Zuoying; Yuan, Tingting; Chen, Jiayi; Jiang, Mihan; Yan, Rongling; Yang, Wencai; Wang, Liqian; Liao, Yang; Huang, Guowen (Frontiers in Chemistry, 2022)
In order to make better use of two kinds of local dominant plant resources of Ginkgo biloba and Zingiber officinale from Yongzhou of Hunan province, in vitro neuroprotective and antioxidant activities of extracts of Ginkgo biloba leaves and Zingiber officinale rhizome and the correlation between the two kinds of activities were analyzed, then in vivo effects on blood physiology and central nerve cell activity of aged mice were determined after continuous gavage with the best polarity part of extract at different concentrations (2, 4, 8 mg/mL). The results showed that the cell survival rate and the superoxide dismutase (SOD) activityof of the induced injury central neurons increased though Malondialdehyde (MDA) content decreased gradually with the increasing of the extracts concentration in a certain range. Different polarity parts showed different performance even at the same concentration, and Ginkgo biloba performed better than Zingiber officinale rhizome when they have same concentration and polarity. the effect order of Ginkgo biloba extract from superior to inferior was ethanol, ethyl acetate, n-butanol, chloroform, water and petroleum ether (except the petroleum ether part was slightly better than the water part at 0.4 mg/mL and 0.5 mg/mL), the order of Zingiber officinale rhizome was ethanol, chloroform, n-butanol, ethyl acetate, water and petroleum ether. These two plant extracts showed good in vitro effect against oxygen free radicals, and scavenging rate of superoxide free radical showed a significant positive correlation with the cell survival rate. The activity of central nerve cells and SOD, Glutathione peroxidase (GSH-PX) in aged mice blood serum increased while the MDA content decreased significantly with the treating of these two extracts(P<0.05). There were no significant changes in the number of leukocytes, lymphocytes, red blood cells, the content of hemoglobin, blood urine nitrogen, uric acid, creatinine, and the enzyme activity of aspartate amino transferase and alanine amino transferase (P>0.05). As same as in vitro, Ginkgo biloba performed better than ginger rhizome when their concentration and polarity part are same. The results provide some references for the development of the two plant extracts from Yongzhou in the field of neuroprotection.